TRANSFORMASI TRADISI LISAN MELAYU SAMBAS KE BENTUK NASKAH DRAMA - Gunawan, Gunawan; Effendy, Chairil; Syam, Christanto (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study analyzes the story of Bujang Nadi dan Dara Nandong and its form of story transformation. The intended form of transformation is the script of Bujang Nadi dan Dare Nandung story. The form of transformation is analyzed based on the content and various forms of affirmation, negation, and story innovation. In addition, this study also analyzes the effects of the story of Bujang Nadi dan Dara Nandong itself. The research method used is descriptive with a form of qualitative research. The results of data analysis found that there are two forms of drama script transformation. They are script of Bujang Nadi Dare Nandung written by Sataruddin Ramli and the script of Bujang Nadi dan Dare Nandung Hidup di Istana Mati dalam Bencana written by Vinny Innayasari and Rahmanita Maulidya. There are additional plot, conflict, and character in both forms of the story transformation. In transformation of scripts written by Sataruddin Ramli, There are five forms of affirmations, three forms of negation, and two forms of story innovation, while in scripts written by Venny Innayasari and Rahmanita Maulidya hasfive forms of affirmation, two forms of negation, and two forms of story innovation. The impacts of transformation for the community in this study are economic, social and cultural impacts, while the impact on oral traditions is related to the oral tradition itself and the dissemination of the oral tradition.Keywords: Transformation, Oral Tradition, Sambas Malay